Vliv přídavku ethenu na aktivitu Z-N katalyzátoru pro nízkotlakou polymeraci propenu - Hoza, Adam (Vysoké učení technické v Brně. Fakulta chemická, 2010)
Náplní práce bude aplikací dvou různých experimentálních postupů vyhodnotit kinetické profily polymerací propenu, ethenu a jejich směsi na komerčním Zieglerovu-Nattovu katalyzátoru. Následně pak bude pomocí SEC analýzy stanovena koncentrace aktivních polymeračních center. Vlastnosti a charakter těchto aktivních center bude dále detailněji studován metodou rozkladu distribučních křivek molekulových hmotností na základní Floryho distribuční funkce. Výsledkem bude ucelená studie o povaze a chování různých typů aktivních center v závislosti na čase a typu monomeru.

The aim of the study will be the determination of the kinetic profiles of the polymerization of propene, ethene and their mixtures with commercial Ziegler-Natta catalyst by application of two different experimental procedures. The prepared polymer material will be utilized for the SEC analysis and subsequent evaluation of the concentration of active sites. The determined molecular mass distribution curves will be further investigated by the application of the procedure, which deconvolute the overall profile on the basic Flory's distribution functions. Then the comprehensive study about character and behavior of various types of active centers in dependence on time and type of monomer will result from this investigation.
Influence of Ethene Addition on Ziegler-Natta Catalyst Performance in Low-pressure Propene Polymerization
Keywords: kopolymerace; propen; ethen; Zieglerovy-Nattovy katalyzátory; kinetika polymerací; copolymerization; propene; ethene; Ziegler-Natta catalysts; polymerization kinetics